Analysis of Geometry Concept Sequence in Student Textbooks Based on Van Hiele's Theory - Janah, Miftakul; Rahardi, Rustanto; Rahardjo, Swasono (Universitas Suryakancana, 2024)
This study aims to analyze the order of textbooks based on van Hiele's theory. The research approach used is descriptive qualitative. The method used is content analysis or content study. The data subject in this research is junior high school mathematics textbook grade VIII curriculum 2013. The research was conducted by looking at the suitability of the characteristics at each van Hiele level with the textbook. Then if a discrepancy is found in the analysis, a solution is given according tZo the researcher's skills. The results showed that in general all the material